The Implications of Intimate Relationships on the Balance between Academic Achievement and Religiosity: A Phenomenological Study - Fadillah, Anif; Jannah, Fathul; Afandi, Nur Kholik (FKIP Universitas Wisnuwardhana, 2026)
This study aims to explore students’ subjective experiences in interpreting and managing intimate relationships and their implications for the balance between academic achievement and religiosity. This study employed a qualitative phenomenological approach involving 22 participants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Interpretative Phenomenological Analysis (IPA). The findings reveal that intimate relationships are ambivalent in nature. On the one hand, they function as sources of emotional support, academic motivation, and spiritual strengthening. On the other hand, they may lead to psychological stress, academic distraction, and moral conflict. The results indicate that the balance between academic achievement and religiosity is not determined by the presence of the relationship itself, but by self-regulation, emotional maturity, and spiritual awareness. This study contributes to Islamic educational psychology by positioning intimate relationships as an integrative space connecting emotional, academic, and spiritual dimensions.